The social animal - Aronson, Elliot (Worth Publishers, 2012)
'The Social Animal' offers an introduction to modern social psychology. Elliot Aronson probes the patterns and motives of human behaviour, covering topics as diverse as conformity, obedience, politics, and advertising.